Surfactant-free self-assembled mesoscale structures in multicomponent mixtures comprising solids, liquids, and gases: nanoparticles, nanodroplets, and nanobubbles - Sedlák, Marián (Frontiers in Soft Matter, 2023)
This mini review critically discusses self-assembled mesoscale structures (dimensions between molecular and macroscopic) forming in multicomponent mixtures comprising (i) liquids or (ii) liquids and solids or (iii) liquids and gases. The common feature of the discussed structures is absence of surfactants. Covered are solvophobicity-driven mesoscale structures (including metastable ouzo-type particles with finite lifetimes), surfactant-free microemulsions, and bulk nanobubbles. The emphasis is mainly on critical analysis of experimental data and suitability of available experimental methods with focus on unambiguous differentiation between various types of mesoscale structures.